2000
DOI: 10.1021/jf0000981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Selection for Enhanced Bioavailable Levels of Iron in Bean (Phaseolus vulgaris L.) Seeds

Abstract: The bioavailability of Fe from 24 select genotypes of bean (Phaseolus vulgaris L.) seeds containing a range of concentrations of Fe, myo-inositol pentaphosphate plus phytic acid (IP5+IP6), and tannins was studied using a rat model. Bean accessions, selected from field trials for their variations in Fe, phytate, and tannin seed concentrations, were grown in a greenhouse in nutrient solutions radiolabeled with (59)Fe. Mature seeds were autoclaved and lyophilized. Test meals (containing 1 g of dried bean, 0.5 g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
2
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 20 publications
12
95
2
14
Order By: Relevance
“…The grain legumes, on the contrary, have a high starting point from where to seek improvements. Beans are superior to cereals in their macro-and micronutrient content as demonstrated in Table 1, in agreement with [9] although trials with other pulses under farmers' conditions have demonstrated that genetic potential are not always expressed under more marginal conditions. Furthermore, the legumes holds a potential for entering the diet in a diversity of ways, ranging from the dry mature seeds, to green seeds and pods as well as leaves used as vegetables, see also [10].…”
Section: The Beansupporting
confidence: 70%
“…The grain legumes, on the contrary, have a high starting point from where to seek improvements. Beans are superior to cereals in their macro-and micronutrient content as demonstrated in Table 1, in agreement with [9] although trials with other pulses under farmers' conditions have demonstrated that genetic potential are not always expressed under more marginal conditions. Furthermore, the legumes holds a potential for entering the diet in a diversity of ways, ranging from the dry mature seeds, to green seeds and pods as well as leaves used as vegetables, see also [10].…”
Section: The Beansupporting
confidence: 70%
“…Deshpande et al (1982) verificaram que o conteúdo de taninos em feijões depende em grande parte da presença ou não do tegumento e de sua coloração, como também varia dependendo da espécie do feijão (CHIARADIA; GOMES, 1997). O conteúdo de taninos dos feijões pigmentados inteiros é maior que nos feijões descascados (DESHPANDE et al, 1982) e os feijões brancos possuem quantidades muito baixas (WELCH et al, 2000) enquanto que os vermelhos e os pretos têm níveis significativamente maiores, portanto, a maior concentração de polifenóis é encontrada em cascas de sementes coloridas, porém os feijões vermelhos apresentam maior concentração que os pretos (BRESSANI et al, 1981;BRESSANI et al, 1991).…”
Section: Taninosunclassified
“…Os teores de IP6 + IP5 são similares aos reportados por Welch et al (2000) e House et al (2002) para feijões cozidos sem maceração, porém são superiores aos citados por Villavicencio et al (2000) para feijões cariocas crus e cozidos com água de maceração, e aos reportados por Lombardi-Boccia et al (1998) para feijões brancos crus e cozidos com água de maceração.…”
Section: Fitatosunclassified
“…Legumes are a superior source of minerals compared to cereals (Welch et al, 2000). In Latin America, bean consumption provides 8 to 27% of the necessary K to satisfy the daily nutritional requirement (Pennington & Young, 1990).…”
Section: Introductionmentioning
confidence: 99%